Shoot induction and multiplication of an endangered medicinal plant Rauvolfia serpentina - P.K. Mishra; R. Mehta; S. Shrivastava; L. Lilhore; S. Masodkara; A. Pawar (Environment Conservation Journal, 2011)
Rauvolfia serpentina is an endangered medicinal plant which is used to treat various diseases. Shoot induction and multiplication was achieved from nodal, apical and leaf explants. MS media supplemented with IAA and BAP was found suitable for shoot induction and multiplication. The apical portions of shoot segment gave good results in multiplication. The regenerated shoot when subcultured to same medium shown better proliferation.